(untitled) (Reumatismo, 2013)
Autoinflammatory disorders are characterized by spontaneous episodes of systemic inflammation deriving from inherited defects of the innate immune system. Childhood is usually the lifetime involved in most inherited autoinflammatory disorders, but a moderate number of patients may experience disease onset during adulthood. Herein we report our experience in the clinical and genetic approach to the diagnosis of autoinflammatory disorders in regard of the first 500 pediatric and adult patients evaluated during the period 2007-2012 in our Center, due to histories of periodically-recurring inflammatory attacks, giving emphasis to the differences observed according to patients’age and to the most relevant data differentiating child and adult-onset autoinflammatory disorders in the medical literature.